Workshop Big Data Analysis bagi Mahasiswa Akuntansi di Kota Pontianak: Upaya Peningkatan Aplikasi Teknik Rasio dan Indeks Keuangan - Indriani, Ika Kurnia; Prasetyo, Henri; Cahyowati, Anik; Widodo, Agus; Nugroho, Yohanes Adi; Perdhiansyah, Perdhiansyah; Rukmi, Murti Puspita; Nur, Uray M.; Soraya, Soraya; Mahyus, Mahyus (Nur Science Institute, 2025)
Big data has become a new phenomenon amidst the development of technology and easy access to information. This condition significantly affects research in the field of accounting. Accounting students are academics who have the opportunity to conduct quantitative research. Ratio and index techniques are one step in utilizing the ease of accessing financial reports. However, there are still many accounting students who have not utilized big data due to a lack of knowledge. The purpose of this workshop is to introduce how to use big data analysis techniques easily and quickly. This workshop was held to improve the analytical skills of accounting students with financial data. The evaluation method uses a rubric for assessing financial report analysis practicums. The results of this community service have succeeded in increasing students’ insight and statistical analytical skills using the Microsoft Excel program. A total of 10 participants have applied ratio and index techniques and have completed calculations for 558 municipal financial data in Indonesia.